Weeds. Season five [videorecording (DVD)] - Kohan, Jenji, 1969- (Lionsgate, 2010)
Nancy is pregnant with the child of a powerful politician turned dangerous drug lord, or is she? Doug and Silas are trying to branch out on their own, Andy is looking to score, and Celia attempts to turn the tables on her kidnappers. With enemies out to smoke the Queen of Green, Nancy's sure to find a whole new crop of trouble.